Cardiorespiratory management of Duchenne muscular dystrophy: emerging therapies, neuromuscular genetics, and new clinical challenges. Issue 4 (April 2022) - Birnkrant, David J; Bello, Luca; Butterfield, Russell J; Carter, John C; Cripe, Linda H; Cripe, Timothy P; McKim, Douglas A; Nandi, Deipanjan; Pegoraro, Elena
Summary: The life-limiting complications of Duchenne muscular dystrophy (DMD) include loss of lung function and progressive cardiomyopathy; when patients are treated with assisted ventilation, cardiac function becomes the main determinant of survival. Therapy for DMD is changing rapidly, with the emergence of new genetic and molecular therapeutic options, the proliferation of which has fostered the perception that DMD is a potentially curable disease. However, data for respiratory and cardiac outcomes are scarce and available evidence is not uniformly positive. Patients who share a dystrophin ( DMD ) genotype can have highly divergent cardiorespiratory phenotypes; genetic modifiers of DMD gene expression are a probable cause of respiratory and cardiac phenotypic variability and discordance. In this Personal View, we provide an overview of new and emerging DMD therapies, highlighting the limitations of current research and considering strategies to incorporate cardiorespiratory assessments into clinical trials. We explore how genetic modifiers could be used to predict cardiorespiratory natural history and how manipulation of such modifiers might represent a promising therapeutic strategy. Finally, we examine the changing role of respiratory physicians, cardiologists, and intensive care clinicians on the frontline of a challenging new clinical landscape.